Inherited RORB pathogenic variants: Overlap of photosensitive genetic generalized and occipital lobe epilepsy. (12th March 2020) - Sadleir, Lynette G.; de Valles‐Ibáñez, Guillem; King, Chontelle; Coleman, Matthew; Mossman, Stuart; Paterson, Sarah; Nguyen, John; Berkovic, Samuel F.; Mullen, Saul; Bahlo, Melanie; Hildebrand, Michael S.; Mefford, Heather C.; et al.
Abstract: Variants in RORB have been reported in eight individuals with epilepsy, with phenotypes ranging from eyelid myoclonia with absence epilepsy to developmental and epileptic encephalopathies. We identified novel RORB variants in 11 affected individuals from four families. One was from whole genome sequencing and three were from RORB screening of three epilepsy cohorts: developmental and epileptic encephalopathies (n = 1021), overlap of generalized and occipital epilepsy (n = 84), and photosensitivity (n = 123). Following interviews and review of medical records, individuals' seizure and epilepsy syndromes were classified. Three novel missense variants and one exon 3 deletion were predicted to be pathogenic by in silico tools, not found in population databases, and located in key evolutionary conserved domains. Median age at seizure onset was 3.5 years (0.5‐10 years). Generalized, predominantly absence and myoclonic, and occipital seizures were seen in all families, often within the same individual (6/11). All individuals with epilepsy were photosensitive, and seven of 11 had cognitive abnormalities. Electroencephalograms showed generalized spike and wave and/or polyspike and wave. Here we show a striking RORB phenotype of overlap of photosensitive generalized and occipital epilepsy in both individuals and families. This is the first report of a gene associated with this overlap of epilepsy syndromes.